WOMEN ENTREPRENEURS AND THE GIG WORKFORCE: A FACTOR-BASED STUDY ON HIRING CHALLENGES - P. KIRUTHIGA , P. SANKAR , S. SAIRAM , T. SASIKUMAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The rise of the gig economy has created a flexible labor paradigm that women entrepreneurs increasingly utilize to foster business expansion. Nevertheless, hiring and managing gig workers entails a variety of intricate challenges, especially for women-led businesses contending with financial limitations, legal uncertainties, technology restraints, and competitive disadvantages. This study seeks to investigate and classify the hiring obstacles encountered by women entrepreneurs in the Indian gig economy using a factor-based methodology. A descriptive research approach was employed, and primary data were gathered through structured interviews with 200 women entrepreneurs in the Chennai district. The research employed Exploratory Factor Analysis (EFA) via IBM SPSS Statistics 27 to discern the fundamental characteristics of the issues. Financial constraints, digital and technological barriers, market and competition constraints, legal and compliance issues, and recruitment and selection challenges were the five main factors identified by the results. The observed data was strongly explained structurally by these five components, which together accounted for 62.47% of the variance. The results highlight the necessity for specific initiatives, including digital training, streamlined legislation, enhanced access to qualified gig workers, and support networks to assist women entrepreneurs. This study offers useful insights for platform development and policy formation, and it adds to the limited research on employer-side issues in the gig economy.